1999
DOI: 10.1101/gad.13.8.946
|View full text |Cite
|
Sign up to set email alerts
|

The subcellular localization of PBX1 and EXD proteins depends on nuclear import and export signals and is modulated by association with PREP1 and HTH

Abstract: Nuclear localization of the Extradenticle (EXD) and PBX1 proteins is regionally restricted during Drosophila and mammalian development. We studied the subcellular localization of EXD, PBX, and their partners Homothorax (HTH) and PREP1, in different cell contexts. HTH and PREP1 are cytoplasmic and require association with EXD/PBX for nuclear localization. EXD and PBX1 are nuclear in murine fibroblasts but not in Drosophila Schneider cells, in which they are actively exported to the cytoplasm. Coexpression of EX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
218
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(228 citation statements)
references
References 22 publications
7
218
0
2
Order By: Relevance
“…Questions concerning the possible roles of cytoplasmic HOX proteins or possible regulation of the movement of HOX proteins from the cytoplasm to the nucleus remain almost completely unanswered. A mechanism regulating the movement of the PBX homeodomain protein from the cytoplasm to the nucleus has been described (Abu-Shaar et al, 1999;Berthelsen et al, 1999). The nuclear localization of other transcription factors depends on phosphorylation events (Gauthier-Rouviere et al, 1995), and several HOX proteins have been reported to be phosphorylated (Jaffe et al, 1997;Berry and Gehring, 2000;LaCelle and Polakowska, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions concerning the possible roles of cytoplasmic HOX proteins or possible regulation of the movement of HOX proteins from the cytoplasm to the nucleus remain almost completely unanswered. A mechanism regulating the movement of the PBX homeodomain protein from the cytoplasm to the nucleus has been described (Abu-Shaar et al, 1999;Berthelsen et al, 1999). The nuclear localization of other transcription factors depends on phosphorylation events (Gauthier-Rouviere et al, 1995), and several HOX proteins have been reported to be phosphorylated (Jaffe et al, 1997;Berry and Gehring, 2000;LaCelle and Polakowska, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Currently however, the regulatory regions of the few downstream targets for HOX proteins, including targets such as p21 (Bromleigh and Freedman, 2000), p53 (Raman et al, 2000a), the progesterone receptor (Raman et al, 2000b), or FGF (Care et al, 1996), do not appear to contain PBX-HOX binding sites. Another level of regulation appears to be the finding that localization of the putative cofactor PBX/EXD proteins to the nucleus is dependent on complex formation with MEIS/HTH homeodomain proteins (Abu-Shaar et al, 1999;Berthelsen et al, 1999). Although few studies have examined HOX protein subcellular localization, we have reported previously that both the HOXB6 protein and MSX2, a non-HOX homeodomain protein, undergo a cytoplasmic to nuclear transition during skin development (Stelnicki et al, 1997;Kömü ves et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Such trimers are required for enhancer function in both flies and mice (Berthelsen et al, 1998a;Jacobs et al, 1999;Ryoo et al, 1999;Ferretti et al, 2000). In addition, MEIS/PREP family members are required for the nuclear localization of PBX family proteins (Mann and Abu-Shaar, 1996;Rieckhof et al, 1997;Berthelsen et al, 1999;Saleh et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous data suggest that HPIP activity involves, at least in part, the control of Pbx mediated gene expression (Abramovich et al, 2000). Pbx1 has been shown to constitutively localize to the cytosol by a mechanism that involves its export from the nucleus by the CRM1 receptor (Berthelsen et al, 1999;Abu-Shaar et al, 1999). The presence of Pbx1 in the nucleus is mediated by its association with the homeobox-containing protein Meis1, and depends on the Pbx1 nuclear localization signal (NLS) (Berthelsen et al, 1999;Abu-Shaar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Pbx1 has been shown to constitutively localize to the cytosol by a mechanism that involves its export from the nucleus by the CRM1 receptor (Berthelsen et al, 1999;Abu-Shaar et al, 1999). The presence of Pbx1 in the nucleus is mediated by its association with the homeobox-containing protein Meis1, and depends on the Pbx1 nuclear localization signal (NLS) (Berthelsen et al, 1999;Abu-Shaar et al, 1999). We have previously reported that HPIP localizes mainly to the cytosol (Abramovich et al, 2000).…”
Section: Introductionmentioning
confidence: 99%